GAMBARAN PENERAPAN TOILET TRAINING ORANGTUA YANG MEMILIKI ANAK USIA 2-3 TAHUN DI EDUCATION 21 KULIM DI KOTA PEKANBARU - Nadia Septriani Septriani; Daviq Chairilsyah Chairilsyah; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrck: This study aims to determine the application of toilet training parents with children aged 2-3 years in education 21 kulim pekanbaru city. The population and sample in this study are all parents who have children aged 2-3 years in education 21 kulim totaling 34 parents. Data collection techniques such as likert scale questionnaire, data analysis techniques using a percentage formula, the result of the application of toilet training parents with children aged 2-3 years in education 21 kulim pekanbaru city, as a whole gained percentage was 69,54%, are in the good category, and when viewed from each indicator, the indicator firs stage was 67, 64% are in the good category, the indicator third stage 66,47% are in the good category, stage indicator to four 72,5% are in the good category, the fifth stage of the indicatore is 70,44% in both categories, the sixth stage indicator 67,94% are in the good category, and the last stage indicators gined are percentage 73,92%, are in the category well. Key words: parents, application toilet training